Engineering properties of improved fibrous peat - Ali, F.H.; Sing, W.L.; Hashim, Roslan (2010)
Depending on the soil type, different types of binder have been used to stabilize soft soils nowadays. An essential criterion in the selection of suitable binder is its capability of achieving the desirable soil stabilizing function. For peat soil, it was evident that the engineering properties of the soil can be improved with Portland cement and ground granulated blast furnace slag with siliceous sand acting as filler. The soil stabilization technique is developed in such a way that the cement, slag and siliceous sand are dry mixed with in situ peat soil to form columnar reinforcement in the deep peat ground prior to preloading. When mixed with cement in the soil, the slag which contains silica, alumina and reactive lime is activated and this can accelerate the reactions of cement in peat and improve the stabilization effect. This paper highlights the evidence on the positive effects of the binder at stabilizing peat soil through laboratory mix design and testing investigation. Markedly increase in pH and unconfined compressive strength and significant reduction in linear shrinkage, compressibility and permeability of the stabilized peat were discovered from the results of the investigation.